2017
DOI: 10.1002/jms.3971
|View full text |Cite
|
Sign up to set email alerts
|

An approach to estimate the activation energies of fragmentation occurring in quadrupole collision cell of the mass spectrometer

Abstract: r e v i ew b u t h a s n o t b e e n t h r o u g h t h e c o p y e d i t i n g , t y p e s e t t i n g , p a g i n a t i o n a n d p r o o f r e a d i n g p r o c e s s w h i c h m a y l e a d t o d i f f e r e n c e s b e tw e e n t h i s v e r s i o n a n d t h e V e r s i o n o f R e c o r d . P l e a s e c i t e t h i s a r t i c l e a s d o i : 1 0 . 1 0 0 2 / jm s . 3 9 7 1 T h i s a r t i c l e i s p r o t e c t e d b y c o p y r i g h t . A l l r i g h t s r e s e r v e d .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…While we observed a few functional groups that contained both nitrogen and sulfur (e.g., sulfonamides (0.2–6%), some azoles (0.1–3%)), CHONS compounds tended to be multifunctional with a combination of oxygen-, nitrogen-, and/or sulfur-containing features (Figures S8–S10). An analysis of survival yield to evaluate parent ion stability showed that in general, multifunctional compounds tended to fragment more readily than monofunctional compounds (Figures S14–S16).…”
Section: Resultsmentioning
confidence: 99%
“…While we observed a few functional groups that contained both nitrogen and sulfur (e.g., sulfonamides (0.2–6%), some azoles (0.1–3%)), CHONS compounds tended to be multifunctional with a combination of oxygen-, nitrogen-, and/or sulfur-containing features (Figures S8–S10). An analysis of survival yield to evaluate parent ion stability showed that in general, multifunctional compounds tended to fragment more readily than monofunctional compounds (Figures S14–S16).…”
Section: Resultsmentioning
confidence: 99%